Equilibrium studies on biosorption of cadmium, lead and congo red dye from aqueous solution onto Antigonon Leptopus- Comparison - B.SUDHAKAR; V.SRI DEVI; K.DAYANA; R.SRIKANTH (International Journal of Pharma and Bio Sciences, 2019)
The main objective is to test the ability of Antigonon Leptopus leaf powder as a potential biosorbent for the removal of metals cadmium, lead and Congo red dye from aqueous solution and was investigated by batch biosorption techniques. The chemical properties and morphology of the biosorbent were characterized by means of FTIR, SEM and XRD techniques. The FTIR -Fourier transform infrared Spectrophotometer from 400-4000 cm -1 analysis, spectroscopy (GX (Perkin Elmer, USA)) provides structural and compositional information on the functional groups presented in the sample. The SEM analysis of Antigonon Leptopus leaf powder was carried out to study the porosity and surface structure of biosorbent. Biosorbent can be crystallographically characterized by means of X-ray diffraction (XRD). In the present study, 44, 72 and 104 µm size leaves’ powder was used as biosorbent without any pre-treatment for metals. But in the case of congo red pretreatment was done. The optimum agitation time for cadmium, lead metal and Congo red dye biosorption is 120, 100 and 60 minutes for 20 mg/L concentration. Influence of various operating parameters like agitation time, initial metal and dye concentration, pH of the aqueous solutions, biosorbent dosage and temperature on biosorption were optimized and compared. The results indicated maximum % biosorption of cadmium, lead and Congo red dye using Antigonon Leptopus were 82.33, 75.00 and 92.35 respectively at optimized conditions. The optimum pH of the aqueous solutions for cadmium, lead and Congo red dye biosorption are 4, 6 and 5 respectively. The optimum biosorbent dosage for the cadmium, lead and Congo red dye biosorption is 1.5, 1.5& 1.0g.The morphology of the different compounds of Antigonon leptopus was studied by the mechanism proposed which involved hydrogen-bonding formations that show the importance of carboxylic groups in the biosorption process. The results demonstrated that Antigonon Leptopus potential and low-cost adsorbent possessed strong sorption characteristics for Congo red dye compared to cadmium and lead ions.